The guilty [videorecording (DVD)] - Möller, Gustav; Cedergren, Jakob; Dinnage, Jessica; Shargawi, Omar (Magnolia Home Entertainment, 2019)
Alarm dispatcher and former police officer Asger Holm answers an emergency call from a kidnapped woman. When the call is suddenly disconnected, the search for the woman and her kidnapper begins. With the phone as his only tool, Asger enters a race against time to save the endangered woman. But soon he realizes that he is dealing with a crime that is far bigger than he first thought.